Comparison of Admission Lung Ultrasound and Left Ventricular End-Diastolic Pressure in Patients Undergoing Primary Percutaneous Coronary Intervention. (19th April 2021) - Neves de Araujo, Gustavo; Beltrame, Rafael; Pinheiro Machado, Guilherme; Luchese Custodio, Julia; Zimerman, Andre; Donelli da Silveira, Anderson; Scolari, Fernado Luís; Corsetti Bergoli, Luiz Carlos; Gonçalves, Sandro Cadaval; Pereira Lima Marques, Felipe; Fuchs, Felipe Costa; Vugman Wainstein, Marco; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Left ventricular end-diastolic pressure (LVEDP) is related to ventricular dysfunction and increased retrograde pulmonary capillary pressure. Lung ultrasound (LUS) is a sensitive and easy-to-use method for assessment of pulmonary congestion. Both methods have shown prognostic value in patients with ST-segment–elevation myocardial infarction. Our aim was to evaluate the correlation between LVEDP and bedside LUS and to compare their prognostic value in patients undergoing primary percutaneous coronary intervention. Methods: Prospective cohort study of ST-segment–elevation myocardial infarction patients treated in a tertiary care hospital in Brazil. LUS was performed immediately before coronary angiography. LVEDP was recorded before primary percutaneous coronary intervention, blinded to LUS results. Primary outcome was any in-hospital major adverse cardiovascular event, defined as in-hospital mortality, new myocardial infarction, stroke, and new cardiogenic shock. Results: In total, 218 patients were included; their mean age was 60 (±12) years, and 64% were men. Cardiogenic shock was present in 16.5% of patients on admission. Overall in-hospital mortality was 15%. Median LVEDP was 19 mm Hg (interquartile range, 13–28); median LUS zones positive for pulmonary congestion were 1/patient (interquartile range, 0–5); Spearman correlation between them was 0.33 ( P <0.001). LVEDP and LUS C statistic for in-hospital major adverse cardiovascular event was 0.63 ([95% CI, 0.55–0.70] P =0.002) and 0.71 ([95% CI, 0.64–0.77] P <0.001), respectively. In multivariable analysis, LUS remained associated with in-hospital major adverse cardiovascular event (odds ratio, 1.14 [95% CI, 1.06–1.23]; P =0.01) for every positive LUS zone; LVEDP, however, did not (odds ratio, 1.01 [95% CI, 0.99–1.03]; P =0.23). Conclusions: We found a weak correlation between LVEDP and LUS in our cohort of ST-segment–elevation myocardial infarction patients undergoing primary percutaneous coronary intervention. Pulmonary congestion in acute heart failure is a complex pathophysiological process and goes beyond fluid overload and hemodynamics. Unlike LVEDP, LUS was significantly associated with in-hospital major adverse cardiovascular event, new cardiogenic shock, and in-hospital mortality in multivariable analysis.